Massive integration of large gene libraries in the chromosome of Escherichia coli - Lidia Cerdán; Beatriz Álvarez; Luis Ángel Fernández (Microbial Biotechnology, 2024)
Abstract Large gene libraries are frequently created in Escherichia coli plasmids, which can induce cell toxicity and expression instability due to the high gene dosage. To address these limitations, gene libraries can be integrated in a single copy into the bacterial chromosome. Here, we describe an efficient system for the massive integration (MAIN) of large gene libraries in the E. coli chromosome that generates in‐frame gene fusions that are expressed stably. MAIN uses a thermosensitive integrative plasmid that is linearized in vivo to promote extensive integration of the gene library via homologous recombination. Positive and negative selections efficiently remove bacteria lacking gene integration in the target site. We tested MAIN with a library of 107 VHH genes that encode nanobodies (Nbs). The integration of VHH genes into a custom target locus of the E. coli chromosome enabled stable expression and surface display of the Nbs. Next‐generation DNA sequencing confirmed that MAIN preserved the diversity of the gene library after integration. Finally, we screened the integrated library to select Nbs that bind a specific antigen using magnetic and fluorescence‐activated cell sorting. This allowed us to identify Nbs binding the epidermal growth factor receptor that were not previously isolated in a similar screening of a multicopy plasmid library. Our results demonstrate that MAIN enables large gene library integration into the E. coli chromosome, creating stably expressed in‐frame fusions for functional screening.